Levels of Tc17 cells in thymic epithelial cell tumors associated with autoimmune diseases - Li, Jian; Chen, Yuan; Wang, Yuanguo; Liu, Yimei; Zhang, Peng (Mediastinum; Vol 3 (March 2019): Mediastinum, 2019)
Background: Thymomas are thymic epithelial cell tumors. Between 4% and 7% of thymomas develop in patients with two or more concomitant diseases of the thymus, the vast majority of which are autoimmune disorders such as myasthenia gravis (MG). Tc17cells and Th17cells have been shown play an important role in the development of tumors and autoimmune diseases (ADs). Methods: We assessed the distribution of Tc17cells in thymic epithelial tumors and the thymic expression of retinoid-related orphan receptor-γt (RORγt) in patients with thymic epithelial tumors as well as MG or other ADs. We also assessed the frequency of Th17/Tc17 cells in peripheral blood mononuclear cells (PBMCs). Results: CD8+ cell frequency, the CD4+/CD8+ T ratio, and levels of immunoglobulin, C-reactive protein (CRP) and complement C3 can be used as indicators of the immune status of patients with thymic epithelial tumors. RORγt mRNA is a key mediator of Th17/Tcl7 cell differentiation, and may play an important role in development of thymic epithelial tumors associated with ADs or disorders. In thymic epithelial tumor tissues, Tc17 cell frequencies were significantly higher in patients with thymomas alone compared with patients with thymomas as well as MG or other ADs (P